Take Apart in Sufistic Literature of Pre-Modern and Modern in West Kalimantan - Khairul Fuad (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
Islamic mysticism has colored the development of West Borneo literature, either pre- modern or modern literature. Sastra kitab is a form of pre-modern Islamic mysti- cism, whereas modern literature has been acostumed to form of Islamic mysticism in modern era. Islamic mysticism and literature has had mutual relationship to develop the discourse themselves. West Borneo that had deep correlation with Malay culture could not be free from Islam due to the identical of Malay and Islam. Acculturation of Malay-Islam has given significant influence for Malay culture, including Islamic mysticism literature that has developed discourse of West Borneo Literature. There- fore, Islamic mysticism literature as one side of globally frame of Islam that has given influence within Malay culture were needed to be researched to show the spirituality of West Borneo literature. Furthermore, methodological frame has had to apply as a scientific step to know West Borneo Islamic mysticism literature. This study uses library and field research in order to collect and describe the data.